Biological Risk Assessment of Heavy Metals in Sediments and Health Risk Assessment in Marine Organisms from Daya Bay, China - Zexing Kuang; Yangguang Gu; Yiyong Rao; Honghui Huang (Journal of Marine Science and Engineering, 2020)
The concentrations of heavy metals in sediments and marine organisms in Daya Bay were investigated, and the Monte Carlo method was used to analyze the uncertainty of the results of geo-accumulation characteristics and ecological and health risks. The mean concentrations of metal elements in sediments were in the following order: Zn > Cr > Cu > As > Cd > Hg, while those in marine organisms were Zn > Cu > As > Cr ≈ Cd > Hg. The geo-accumulation index (Igeo) indicated that the primary pollutant was Hg, with 5.46% moderately polluted, and 39.52% for unpolluted to moderately polluted. Potential ecological risks (RI) were between low and high risks, and the contributions of Hg, Cd, and As to ecological risks were 50.85%, 33.92%, and 11.47%, respectively. The total hazard coefficients (THQ) were less than 1, but on the basis of total carcinogenic risks (TCR), the probability of children and adults exceeded the unacceptable risk threshold of 22.27% and 11.19%, respectively. Sensitivity analysis results showed that the concentrations of carcinogenic elements contributed to risk in the order of As > Cd > Cr. Therefore, in order to effectively control heavy metals contamination in Daya Bay, it is necessary to strengthen the management of Hg, Cd, and As emissions.